Pengaruh E-Service Quality dan Nilai Pelanggan Terhadap Keberhasilan Usaha (Studi Kasus Usaha Dagang MP. Rambe) - Rambe, Barita Jogi; Aisyah, Nur; Lubis, Adelina (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2023)
The purpose of this research is to find out and analyze whether e-service quality and customer value influence business success in MP trading businesses. Rambe in Pinangsori. This research uses associative research, where associative research takes the form of a quantitative approach which is seen from the type of data which is measured using a Likert scale. The population in this study was 100 customers. The sample in this study used saturated purposive sampling. Data processing uses SPSS 26, by testing the partial linear regression analysis hypothesis (t test) it can be seen that the calculated t for the e-service quality variable is 2.687 t table 1.984. Meanwhile, the customer value variable is 3.727 t table 1.984 and the significance level is smaller than 0.5. This shows that HO is rejected and H1 is accepted. And the coefficient of determination results show an Adjusted R Square value of 0.374 or 37.4%. Based on these overall values, e-service quality and customer value have a positive and significant effect on business success.